2021
DOI: 10.1155/2021/5471281
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Observation of Levothyroxine Sodium Combined with Selenium in the Treatment of Patients with Chronic Lymphocytic Thyroiditis and Hypothyroidism and the Effects on Thyroid Function, Mood, and Inflammatory Factors

Abstract: The purpose of this study was to investigate the therapeutic effects of levothyroxine sodium combined with selenium treatment and single levothyroxine sodium treatment on patients with chronic lymphocytic thyroiditis and hypothyroidism and to analyze the effects of different treatment regimens on patients’ thyroid function, mood, and inflammatory factors, with the aim of providing a reference for clinical treatment. The subjects of the current study were 138 chronic lymphocytic thyroiditis (CLT) patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…This relatively high rate of prescription may result from the acquaintance of several studies that advocate Se benefits in Hashimoto's treatment (Table 1). Some of the latest [27,28,31,34], have consistently shown that Se-Su treated HT patients have reduced thyroid autoantibodies and TSH levels. A 2016 systematic review and meta-analysis of 16 studies [17] also concluded that Se-Su significantly reduces serum antibodies levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This relatively high rate of prescription may result from the acquaintance of several studies that advocate Se benefits in Hashimoto's treatment (Table 1). Some of the latest [27,28,31,34], have consistently shown that Se-Su treated HT patients have reduced thyroid autoantibodies and TSH levels. A 2016 systematic review and meta-analysis of 16 studies [17] also concluded that Se-Su significantly reduces serum antibodies levels.…”
Section: Discussionmentioning
confidence: 99%
“…Se-Su, however, is not considered in the guidelines from the American Thyroid Association (ATA), probably because Se levels tend to be considerably higher in North America and lower in many European countries. Nevertheless, several trials and studies have continued the investigation of Se-Su effects in different AITDs ( Table 1 ) ( 15 , 16 , 17 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ). Overall, in patients with HT, Se-Su has resulted in higher antioxidant activity ( 27 ), reduced thyroid autoantibody titre ( 34 ), lower levels of thyroid-stimulating hormone (TSH) ( 32 ), higher Tregs ( 32 ), and reduced expression of proinflammatory cytokines ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent animal study found that when mice were placed on a low selenium diet (0.02 mg/kg), selenium levels in the thyroid gland were maintained, but reduced selenoprotein expression was observed in the liver and kidneys, targets of thyroid hormones [ 214 ]. While selenium supplementation was reported to induce no significant therapeutic effect on patients with subclinical hypothyroidism [ 215 ], co-treatment of selenium was found to enhance the efficacy of levothyroxine sodium (LT4) in treating chronic lymphocytic thyroiditis patients with hypothyroidism, yielding greater improvements to inflammatory factors, compared to treatment with LT4 alone [ 216 ]. Selenium supplementation was also found to increase the efficacy of antithyroid drugs in the treatment of Graves’ disease [ 217 ].…”
Section: Signals From Brain To Bodymentioning
confidence: 99%
“…Selenium has been reported to be associated with various inflammatory diseases [21][22][23][24][25][26][27][28] such as inflammatory bowel disease, 26 experimental colitis, 24 chronic lymphocytic thyroiditis and hypothyroidism. 25 Federico Galusso et al 29 reported that low plasma selenium status and Development or risk of severe active inflammatory disease, such as systemic inflammatory response syndrome and multiple organ dysfunction syndromes, are closely linked. In addition, individuals with asthma, a chronic inflammatory disease, have been reported to have lower selenium status and decreased activity of glutathione peroxidase.…”
Section: Figurementioning
confidence: 99%